Correction: Antimicrobial resistance genotypes and phenotypes of Campylobacter jejuni isolated in Italy from humans, birds from wild and urban habitats, and poultry. - Francesca Marotta (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0223804.].